Effect of ultrasonic cavitation on grain growth of ceramic tool materials - LI Dong-xu; SONG Jin-peng; GAO Jiao-jiao; LÜ Ming (Fenmo yejin jishu)
To investigate the effect of the ultrasonic cavitation on the grain growth of the ceramic tool materials during the ultrasonic pressureless sintering, the cavitation effect of bubbles in the molten metals was studied, the grain model containing the cavitation bubbles was established, and the grain growth process without and with ultrasound was simulated by Monte Carlo method. The results show that, the threshold of sound pressure is 8.02×106 Pa and the threshold frequency is 2.00×106 Hz when the radius of the cavitation bubble is between 1 μm and 2 μm. Furthermore, the ultrasonic cavitation can increase the vibration frequency and vibration energy of the lattice, which hinders the growth of the crystal grains, refines the grains, and reduces the pore size.